Dual-readout fluorescence quenching immunochromatographic test strips for highly sensitive simultaneous detection of chloramphenicol and amantadine based on gold nanoparticle-triggered photoluminescent nanoswitch control - Xiong, Jincheng; He, Shuang; Wang, Zile; Xu, Yuliang; Zhang, Liang; Zhang, Huixia; Jiang, Haiyang (Journal of hazardous materials, 2022)
Herein, a novel fluorescence quenching immunochromatographic test strip (FQICTS) for simultaneous detection of chloramphenicol (CAP) and amantadine (AMD) was developed on the basis of inner filter effect (IFE), with the combination of gold nanoparticles (AuNPs) and highly luminescent green-emitting gold nanoclusters (AuNCs) as the IFE quencher/donor pair. The AuNPs could quench the excitation light and emission light of AuNCs and achieve a high IFE efficiency due to dual spectral overlapping. Under optimal conditions, the “turn-on” mode of the AuNCs-based dual-readout FQICTS showed good linearity for CAP detection in chicken samples from 0.05 ng/g to 10 ng/g, with a limit of detection (LOD) of 0.043 ng/g. The linear range of AMD is 0.5–50 ng/g, with LOD of 0.45 ng/g. The visual LODs of CAP and AMD in “turn-on” mode were 200 and 10 times lower than that in “turn-off” mode, respectively. The “turn-on” mode of FQICTS showed high recovery for detecting CAP (82.5–94.5%) and AMD (81.9–110.7%) spiked into chicken samples. The performance and practicability of the established method were verified with commercial enzyme-immunoassay kits, and good correlations were observed. Overall, the newly developed AuNCs-based dual-readout FQICTS is a promising on-site screening tool for rapid, high-sensitivity detection of multiple food contaminants in practical applications. [Display omitted] •Highly luminescent green-emitting AuNCs was firstly employed as fluorescent donor for constructing FQICTS.•The excitation light and emission light of the fluorescent donor could be quenched by IFE generated between AuNPs and AuNCs.•Dual-signal readout, fluorescence quenching signal amplification, and simultaneous detection of CAP and AMD.•High-sensitive detection of CAP and AMD with LODs of 0.043 ng/g and 0.45 ng/g in chicken samples, respectively.